Data on the vegetative growth at post acclimatization stage of two dendrobium genotypes as an effect of different growing media - Yayat Rochayat Suradinata; Murgayanti; Erni Suminar; Anne Nuraini; Jajang Sauman Hamdani; Syariful Mubarok (Data in Brief, 2019)
The growing medium is an important factor for plant growth and development. Many growing media are used for orchids, but their availability is limited and some are prohibitively expensive. Therefore, alternative growing media need to be studied. This study was conducted to investigate the potency of some alternative growing media for growing two Dendrobium genotypes, D. sylvanum and D. nindii x D. stratiotes, at the post-acclimatization stage. Five growing media were used in this experiment, namely tree fern fibers, coconut fibers, sphagnum moss, asplenium root, and calliandra humus.